Infusion of C20:0 ceramide into ventral hippocampus triggers anhedonia-like behavior in female and male rats - Sambolín-Escobales, Lubriel; Feliciano-Quiñones, Adariana; Tirado-Castro, Lizmarie; Suárez, Cristina; Pacheco-Cruz, Dariangelly; Irizarry-Méndez, Nashaly; Fonseca-Ferrer, Wilfred; Hernández-López, Anixa; Colón-Romero, María; Porter, James T. (Frontiers in Behavioral Neuroscience, 2022)
Increased long-chain C20:0 ceramides have been found in the serum of patients with depression. Moreover, ceramides are linked with increased microglia reactivity and inflammatory cytokine production, which are associated with depression. Since ceramides can readily cross the blood brain barrier, peripheral C20:0 ceramides could enter the brain, activate microglia, and induce depressive-like behavior. In this study, we determined whether localized infusion of C20:0 ceramides into the ventral hippocampus (VH) of rats is sufficient to activate microglia and induce depressive-like behaviors. Adult male and female rats received infusions of C20:0 ceramides or vehicle solution every other day for 2 weeks. After the third infusion, C20:0-infused animals showed reduced sucrose preference suggesting anhedonia-like behavior. In contrast, infusions of C20:0 ceramides did not affect immobility in the forced swim test or sucrose grooming suggesting that the behavioral effects of ceramides are task dependent. Furthermore, C20:0-infusions did not increase Iba-1+ microglia or inflammatory markers in the VH suggesting that localized increases in C20:0 ceramides in the VH are sufficient to induce anhedonia-like behavior without microglia activation.